Late Devonian-early Carboniferous bryozoans from Zhankurgan (Greater Karatau, Kazakhstan)—taxonomy and palaeobiogeographical implications - Tolokonnikova, Zoya A.; Fedorov, Petr V. (Zootaxa, 2022)
Three bryozoan species Anomalotoechus sp., Pseudobatostomella sp. and Cyphotrypa sp. are described from the upper part of the Ermaksy Formation (lower-middle Famennian) of the Zhankurgan outcrop (Greater Karatau). These descriptions are important, because it is the first finding of upper Devonian bryozoans in Southern Kazakhstan. Five more species including one new Primorella zhankurganica sp. n. were found in limestones of the lower part of Orgalysay Formation (Upper Tournaisian) in the same outcrop. The hitherto known bryozoans from the Tournaisian of Greater Karatau constitute the most important bryozoan fauna from the carbonate platform, located on southwestern passive margin of the Kazakhstan palaeocontinent. The studied fauna reveals connections between different areas of Palaeotethys and Palaeoasian oceans in late Devonian-early Carboniferous.